Therapeutic and Diagnostic Value of Caspase-12 and Study of Growth Differentiation Factor-15 in Patients with Acute Myocar-dial Infarction - Changqing SUN; Xiulin LI; Daoqing WANG; Liming WANG (Tehran University of Medical Sciences, 2020)
Background: To investigate the therapeutic and diagnostic value of caspase-12 and study of growth differentiation factor-15 (GDF-15) in patients with acute myocardial infarction (AMI). Methods: Overall 78 patients with AMI admitted to Weifang People's Hospital Brain Hospital, Weifang, China from Apr 2016 to Apr 2019 were enrolled as AMI group. Seventy five non-AMI people undergoing physical examination during the same period were enrolled as non-AMI group. The expression levels of caspase-12 and GDF-15 were detected and compared. The correlation between the expressions of GDF-15, caspase-12 and clinical characteristics and efficacy was detected. Single and combined detection of GDF-15 and caspase-12 were performed analyze their role in the early diagnosis, the prediction of efficacy, and the guidance of clinical therapy. Results: After treatment, the levels of GDF-15 and caspase-12 in AMI group were significantly lower than those before treatment (P<0.001). The expression levels of GDF-15 and caspase-12 were significantly correlated with blood pressure (P<0.05). The expression levels of GDF-15 and caspase-12 were significantly negatively correlated with clinical efficacy in AMI group. The diagnostic value of combined detection of GDF-15 and caspase-12 was higher than that of single diagnosis. The levels of serum caspase-12 and GDF-15 proteins were significantly up-regulated in AMI patients. With the better therapeutic effect, the levels of serum caspase-12 and GDF-15 proteins decreased significantly. Conclusion: The levels of serum caspase-12 and GDF-15 proteins may be a key indicator in the clinical diagnosis of acute myocardial infarction and may also be used to guide the treatment of AMI patients and predict the therapeutic efficacy.